Reducing CLABSI through a quality strategy for the implementation of the aseptic non-touch technique in a pediatric ward - Ana C. Guerrero-Díaz; Daniela de la Rosa-Zamboni; Ma. A. Martin-Martin; Isabel Rosas-Mateos; Marisol Medina-Pelcastre; Margarita Torres-García; Almudena Laris-González; Martha Avilés-Robles (Permanyer, 2024)
Background: Central line-associated bloodstream infections (CLABSIs) are among the most epidemiologically relevant health care-associated infections. The aseptic non-touch technique (ANTT) is a standardized practice used to prevent CLABSIs. In a pediatric hospital, the overall CLABSI rate was 1.92/1000 catheter days (CD). However, in one unit, the rate was 5.7/1000 CD. Methods: Nurses were trained in ANTT. For the implementation, plan-do-study-act (PDSA) cycles were completed. Adherence monitoring of the ANTT and epidemiological surveillance were performed. Results: ANTT adherence of 95% was achieved after 6 PDSA cycles. Hand hygiene and general cleaning reached 100% adherence. Port disinfection and material collection had the lowest adherence rates, with 76.2% and 84.7%, respectively. The CLABSI rate decreased from 5.7 to 1.26/1000 CD. Conclusion: The implementation of ANTT helped reduce the CLABSI rate. Training and continuous monitoring are key to maintaining ANTT adherence.